Influence of tiotriazoline on the infringed cytokin profile indicators in the six period of formation of pulmonary patients with haulage of experimental pneumonia - L. O. Furdychko (Kazimierz Wielki University, 2017)
Respiratory and digestive diseases are quite common and have a tendency to constant growth. A special place among the significant number of pathology of the broncho-pulmonary apparatus of inflammatory genesis is pneumonia (P), and among diseases of the digestive tract - ulcerative stomach disease (VHSh). For many years, both the clinicians and the experimenters have studied the pathogenesis of these diseases. For the experiment, we selected two models of disease: experimental pneumonia (EP) and peptic ulcer (PU). For the correction of cytokine disorders, we selected tiotriazoline, which exhibits antioxidant, anti-ischemic, membrane-stabilizing and immunomodulatory effects. Materials and methods. The study was conducted on 49 male guinea pigs, weighing 180 - 210 g test animals were divided into four groups. The experimental pneumonia caused by the method Shlyapnykova V. N., Solodova T. L., gastric ulcer simulated method Komarov V. I. All guinea pigs carried determine the concentration of cytokines: TNF-α, IL-6 and IL-10 in serum using ELISA (ELISA) using the kits of the company «Diaclone» (France), according to the enclosed instructions. Digital statistical results processed by using Student's criterion. The use of the drug thiotriazoline in a dose of 100 mg per 1 kg of daily basis. Results and discussion. In the study of the system EP and cytokines in PU found that in the test day of the experiment were as likely changes in the content of proinflammatory and antiinflammatory cytokines compared with the group of intact animals .The results of the study of the cytokine profile in the blood serum under the conditions of PU+EP, established an increase in the concentration of proinflammatory central nervous system, especially on the 18th formation of these models of diseases in accordance with the animals of the first group. The study of anti-inflammatory cytokine (IL-10) has established its depression, which indicates the depletion of protective properties of the body. The use of immunoregulatory, antioxidant and membrane-titer preparations of thiotriazolin resulted in a decrease in the reduction of proinflammatory cytokines, which led to an increase in the level of interleukin-10, which suppresses the production of proinflammatory cytokines.